Alpha track distribution on lateral wall of cylindrical radon diffusion chamber. (February 2022) - Markovic, V.M.; Stajic, J.M.; Milenkovic, B.; Stevanovic, N.
Abstract: Cylindrical diffusion chamber with solid state nuclear track detector placed at the bottom of the chamber is frequently used device for measuring radon concentration in dwellings. In this work, the diffusion chamber with CR-39 detector was modeled to determine track distribution on the lateral (cylinder) wall of the chamber and compare track density between cylinder wall and bottom. Model is based on the diffusion, deposition and decay of radon and its progeny in diffusion chamber. Equations for criteria of track visibility and track density were derived. Along with theoretical model, measurements were performed to verify the theoretical results. Three different chambers with CR-39 detectors slabs attached along the cylinder wall were investigated. It was found that alpha track density on cylinder wall is not uniform and depends on the shape and size of the chamber. Deviation of track density along cylinder wall was up to 30% for chambers used in this work. Sensitivity of the cylinder wall was found to be almost the same as the sensitivity of the bottom. In comparison with the experiment, theoretical results give good predictions. Along with previous results of the authors where bottom track density was modeled, presented model can be used for calibration and optimization of the diffusion chambers used for radon measurements. Highlights: Distribution of alpha particle tracks on lateral wall of diffusion chamber is theoretically modeled and experimentally measured. Track density distribution exhibits complex dependence on chamber dimensions and is not uniform. Detector response functions and critical angle are verified. Theoretical model for calibration of cylinder diffusion chamber is developed.